Wen-Shen-Tong-Luo-Zhi-Tong Decoction alleviates bone loss in aged mice by suppressing LONP1-mediated macrophage senescence - Qinfeng Zhou; Kaixuan Wang; Cong Wang; Xiaoxian Sun; Lining Wang; Jie Sun; Yalan Pan; Muzhe Li; Zitong Zhao; Shijie Zhou; Qing Wang; Yafeng Zhang; et al. (Pharmaceutical Biology)
Context Aging leads to senile osteoporosis (SOP), marked by bone loss and increased fracture risk. Macrophages, as active immune cells in bone tissue, play an important role in osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) during aging. Wen-Shen-Tong-Luo-Zhi-Tong Decoction (WSTLZTD), a traditional Chinese herbal formula, has been clinically validated for its efficacy in treating SOP. However, the specific mechanisms by which WSTLZTD exerts its anti-SOP effects—particularly through modulating macrophage senescence—remain unclear.Objective The study aims to elucidate the role of WSTLZTD in macrophage senescence and SOP.Materials and methods Aged mice received low, medium, high-dose WSTLZTD. Bone loss was evaluated via micro-computed tomography, hematoxylin and eosin staining and osteocalcin, tartrate-resistant acid phosphatase marker analysis. Macrophage senescence detection (β-galactosidase staining, p16, p21) and molecular mechanisms by Western blot, immunohistochemistry, immunofluorescence method were investigated. Macrophage-conditioned medium’s effects on BMSC osteogenesis and mitochondrial function were assessed through alkaline phosphatase, Alizarin Red S staining, reactive oxygen species and JC-1 mitochondrial membrane potential (ΔΨm) assays.Results In vivo experiments demonstrated that WSTLZTD effectively ameliorated macrophage senescence and osteoporosis in naturally aged mice. Mechanistically, high-dose WSTLZTD attenuated senescence in bone marrow-derived macrophages by mediating LONP1, concurrently suppressing the cyclic GMP-AMP synthase (cGAS)/STING signaling pathway in BMSCs, thereby enhancing osteogenic differentiation of BMSCs. In vitro studies further confirmed that WSTLZTD-containing serum attenuated the senescent phenotype of macrophages. Notably, the LONP1 inhibitor, LONP1-IN-2, was found to diminish the anti-senescence effects of WSTLZTD on macrophages and BMSC osteogenesis.Discussion and conclusion WSTLZTD potentially modulate macrophage senescence via LONP1, which subsequently suppresses the activation of the cGAS/STING pathway in BMSCs, ultimately promoting their osteogenic differentiation and ameliorating osteoporosis.